Penyisihan Total Suspended Solid dan Minyak Lemak pada Air Limbah Rumah Makan Menggunakan Grease Trap dan Filter Biochar Tatal Karet - Hasan, Hadrah; Riyanti, Anggrika; Marhadi, Marhadi; Putri, Ni’mah Khalifah; Jannah, Iptahul (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research was to determine the removal of Total Suspended Solids and fatty oils using the grease trap and filtration methods. Based on the results of experiments that have been carried out, the removal efficiency of Total Suspended Solid at various residence times reached 99.09% (12 hours), 97.89% (24 hours), 98.65% (36 hours), 98.89% (48 hours), 99.18% (60 hours), and 99.3% (72 hours). Fatty oil removal over a period of 12 to 72 hours reached 99.99%. The use of grease traps and filters with biochar rubber and sand media shows that this treatment has proven effective in reducing levels of Total Suspended Solids and fatty oils to meet domestic wastewater quality standards.